(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The present study was carried out to determine the impact of SO2 on Cicer arietinum. SO2 ismost important common air pollutant generally emitted by industries and vehicles on some biochemicalparameters in Chick pea. The concentration of SO2 was determined at the site of D.S. College. The Chickpea showed significant reduction in chlorophyll and carotenoid. It is concluded that the ambient airpollutants have a potential adverse impact on biochemical parameters, which further leads to a reductionin the yield of Chick pea.